Lotus spp.: a Mediterranean genus with high environment and economic impact in the Salado River Basin (Argentina) - Ruiz, Oscar Adolfo (2024)
This review has the principal objective in to hypothesise that the introduction of Lotus species could have significant benefits in constrained soils due their worldwide distribution. This idea is major based on results obtained in the lowlands of the most important livestock breeding area in Argentina denominated Salado River Basin (also called “Flooding Pampas”). Mostly of their land surface is dominated by salt-affected soils with severe constraints for traditional crop cultivation (i.e., maize, soybean, etc.). In order to increase their economic importance, farmers have utilized species such as non-native L. tenuis (ex- Lotus glaber), originating from European Mediterranean area, which shows a successfully and fast naturalization (in less than 60 years) in constrained areas improving forage performance. The increase in soil quality associated to this legume is achieved by an increment of the organic matter content and improvement of fertility and physicochemical parameters. Moreover, other studies have evidenced some genetic determinants associated with interesting agronomic traits such as plant tolerance to environmental stresses and the importance of leaves condensed tannins concentrations. This revision has many topics including a brief analysis of economic and environmental changes that occur under Lotus species implantation. In addition, we incorporate references recently published concerning the evaluation of the biochemical and physiological mechanisms involved in their adaptation to strong abiotic stresses characteristic of the region, the soil and plant microbiota diversity and soil physical and chemical characteristics associated to the presence of Lotus genotypes.